Relationship of Glycemic Status with Disease Severity in Guillain-Barré Syndrome (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Guillain-Barré syndrome (GBS) is an acute autoimmune polyneuroradiculopathy characterized by flaccid paralysis which may lead to respiratory failure requiring intensive care.Objective: The purpose of the present study was to explore the relationship between the fasting plasma glucose (FPG), hemoglobin A1c (HbA1c) and disease severity of GBS patients who are not known to have DM.Methodology: This cross-sectional study included adult GBS patients without having DM [age 35 (22-48) years, median (interqurtile range, IQR); 39 male 22 female] who were admitted to Neurology department, National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from July 2018 to June 2019. Demographics, clinical data were noted and FPG, HbA1c were measured. Disease severity were assessed by the GBS disability scale ranging from 0 to 6 with increasing score reflecting increased disability.Results: Patients with more severe GBS (disability score ≥4, unable to walk) had higher frequency of elevated FPG >5.5 mmol/L (61.2%; 30/49) in comparison to those with less severe GBS (disability score ≤3, able to walk; FPG >5.5 mmol/L in 16.7%, 2/12; p=0.006). But distribution of HbA1c category was not different across the groups (disability score ≥4 vs. ≤3: HbA1c 6.4: 10% vs. 17%; p=0.296). Participants with elevated FPG were elder [elevated vs. normal FPG: 40 (28-54) vs. 25 (19-43) years; median (IQR), p=0.012] and had higher CSF glucose (p=0.002) than those with normal FPG, but there was no difference in respct of gender, MRC sum score, requirement of assisted ventilation, CSF protein, GBS subtypes and duration of hospital stay (p=not significant for all).Conclusions: Patients with severe GBS have higher frequency of elevated FPG but not HbA1c. An acute change in glucose metabolism may occur in GBS which needs further study.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 96-100